A de novo PUM1 Variant in a Girl With a Dravet-Like Syndrome: Case Report and Literature Review - Ye, Yuanzhen; Hu, Zhanqi; Mai, Jiahui; Chen, Li; Cao, Dezhi; Liao, Jianxiang; Duan, Jing (Frontiers in Pediatrics, 2022)
In recent 3 years, subjects with Pumilio1-Associated Developmental Disability, Ataxia, and Seizure syndrome have been identified as harboring Pumilio homolog 1 (PUM1) mutations. However, the characteristics of the seizure phenotype remain to be elucidated. We herein describe a 3-year-old female proband who was diagnosed with developmental and epileptic encephalopathy presenting with some features suggestive of a Dravet-like syndrome. For genetic analyses, trio-based whole-exome sequencing and array comparative genomic hybridization were performed. Consequently, a de novo heterozygous missense variant was identified in exon 22 of the PUM1 gene: NM_001020658: c.3439C＞T (p.Arg1147Trp). Upon thoroughly reviewing the existing literature, nine cases of PUM1 mutation-related epilepsy were identified, and their clinical features were summarized. A relationship between PUM1 mutation and clinical manifestations characteristic of a Dravet-like syndrome was proposed. To our knowledge, this is the first report of a patient with PUM1 mutation presenting with a Dravet-like syndrome.